Assessing potential plants extracts to reduce leucoptera coffeella (Lepidoptera: Lyonetiidae) attack in coffee - Fanela, Thiago Luis Martins [UNESP]; Baldin, Edson Luiz Lopes [UNESP]; Bentivenha, José Paulo Franco; Santana, Alisson da Silva [UNESP] (My University, 2020)
Leucoptera coffeella (Guérin-Méneville) (Lepidoptera: Lyonetiidae) is one of the major pests of coffee in South America, causing severe defoliation in coffee plants. Chemical control has been widely used for the management of this insect. However, this practice is becoming gradually less efficient due to the selection of coffee leaf miner populations resistant to synthetic insecticides. Plants extracts can be a valuable tool for the management of L. coffeella, due to the potential of plants insecticidal properties of them being compatible with the integrated pest management. This study evaluated the effect of nine botanic aqueous extracts on the oviposition and biology of L. coffeella, under laboratory conditions. The extracts of Toona ciliata, Trichilia casaretti and Trichilia pallida decreased the oviposition rate of L. coffeella on coffee leaves. Along with Trichilia catigua, Chenopodium ambrosioides and Melia azedarach, these extracts were classified as deterrent to oviposition by a preference index and the C. ambrosioides, T. casaretti and T. ciliata extracts caused high egg mortality of L. coffeella. Extracts of seeds of A. indica and T. pallida negatively affected the development and survival of L. coffeella, and reduced the mined area by larvae. In conclusion, the extracts of A. indica (S), T. pallida, C. ambrosioides, T. casaretti and T. ciliata exhibited high insecticidal activity and might be useful in integrated management programs for L. coffeella.
Keywords: Coffee leaf miner; Pest management; Plant extracts